Current concepts in sports nutrition - Burke, L.; Bell, L.; Cort, M.; Cox, G.; Farthing, L.; Greenaway, B.; Minehan, M.; Petrunoff, N.; Wood, C. (2004)
List of contents: - Energy balance - Managing body composition - Fuelling up - Pre-event preparation - During exercise - Recovery - Immune function - Dietary supplements